Abatacept treatment shows a modulating effect on Treg subsets in LRBA-deficient patients - Donhauser, Sabine; Salzmann-Manrique, Emilia; Lueck, Leon Maximilian; Fekadu-Siebald, Julia; Schubert, Ralf; Huenecke, Sabine; Bakhtiar, Shahrzad (Frontiers in Immunology, 2026)
There has been tremendous progress in the understanding of subsets of regulatory T cells (Tregs). However, despite their theoretical importance, Treg subsets are not routinely analyzed in patients with immune dysregulation over the course of the disease and treatment. This is particularly the case in pediatric patients when the primary patient material is limited. Here, we used a rapid permeabilization assay to analyze CD4+CD25hiFOXP3+ and CD4+CD25hiCD127low Tregs with subsets including Helios+ Treg, Helios− Treg, Helios+CD39+ Treg, CD62L+CD45RA+ Treg, CD62L+CD45RA− Treg, and FOXP3hiCD45RA− Treg in a predominantly pediatric cohort of patients with an inborn error of immunity (IEI) affecting their Treg compartment due to pathological variants in the lipopolysaccharide-responsive beige-like anchor protein (LRBA) gene. Longitudinal data were collected during abatacept treatment and after allogeneic hematopoietic stem cell transplantation (alloHSCT). Abatacept treatment led to a decrease in Helios− Treg (p = 0.049) over a 10-month treatment period and a significant increase in Helios+ Treg (p = 0.024). This was accompanied by clinical amelioration of disease symptoms, which was captured accordingly using the immune deficiency and dysregulation activity (IDDA2.1) score.